Management of the Cekrekening.id Website as a Supporting Mechanism for Online Transaction Security for the Public - Elizabeth Tawlyn Bogar; Suparman (Yayasan Sinergi Kawula Muda, 2025)
This study examines the operational management of digital fraud report classification on CekRekening.id, a national verification platform administered by the Ministry of Communication and Informatics of Indonesia to enhance online transaction security. The research addresses a clear gap in existing literature, as no prior study has provided an insider, process-level description of how fraud reports are screened, verified, and coordinated with banks through direct participant observation within a government digital service. The objective of this study is to explain the end-to-end workflow of fraud report management and identify key challenges that influence system effectiveness and public adoption. The research employed a qualitative participant-observation method during a three-month internship, supported by informal interviews and documentation review conducted within the institutional verification team. Data were grouped into thematic categories to capture procedures, operational constraints, and user behavior patterns that shaped daily verification work. The findings demonstrate that the platform follows a multi-stage workflow comprising submission, initial screening, verification, bank coordination, and publication, while also revealing critical constraints such as low digital literacy, interface ambiguity, limited staffing, and system performance inconsistencies. These findings highlight gaps between the platform’s technical design and real-world operational demands. The study recommends strengthening digital literacy initiatives, enhancing interface clarity, improving system reliability, and expanding inter-institutional collaboration. Overall, this research contributes a unique operational perspective that can guide future improvements in national digital transaction security.